Teknik Pembelajaran Dasar Tari Melayu Tradisional / editor, Hj. Tengku Mira Rozanna Sinar dan Mahyudin Al Mudra - Tengku Mira Rozanna Sinar, Hj.; Mahyudin Al Mudra (Yayasan Kesultanan Serdang, 2011)
xiv, 102 hlm. : ilus. ; 20 cm.